Criticism of Javacentrism from the Historical Parody of the Film Nagabonar (1986) - Satrio, Satrio Pamungkas; Kurnia, Lilawati; Tjahyandari, Lily; Rusdiarti, Suma Riella (Universitas Negeri Surabaya, 2024)
This paper examines the construction of a dominant discourse criticized by parody in film. The construction of Javanese cultural discourse has been the dominant discourse since the beginning of the Indonesian state; even the meanings born from the construction of the discourse remain to this day. Javanese cultural discourse refers to all forms of discussion related to cultural aspects in Java, including values, norms, traditions, art, language, and local wisdom of the Javanese people. Nagabonar's film deconstructs Javanese discourse with historical parody in its story. This research is expected to open up another way of thinking from the dominance of Javacentric thinking. Two approaches are used to recite and criticize Nagabonar's film as text: cinematographic theory and deconstruction. First is the mise-en-scene approach and staging in cinematographic theory, while the second is the theory of deconstruction to see what history hides or forbids and recasts a discourse construction of thinking that was previously marginalized or even alienated. This study aims to show the meaning of criticism in Nagabonar films against Javacentric dominant discourse through the deconstruction of film texts. Critics of this film tend to open questions about the concept of Indonesian nationalism